Multipoint boundary value problem for a coupled system of psi-Hilfer nonlinear implicit fractional differential equation - Maheswari, Muthukrishnan Latha; Shri, Kolathur Srinivasan Keerthana; Elsayed, Elsayed M. (Nonlinear Analysis: Modelling and Control, 2023)
This study examines the existence and uniqueness of the solution to the coupled system of the ψ-Hilfer nonlinear implicit fractional multipoint boundary value problem. The uniqueness is shown by the Banach contraction principle, and the existence is shown by Krasnosel’skii’s fixed point theorem in a special working space. An example is presented to verify our results. The existence and uniqueness of the solution are analysed graphically.
Keywords: existence; fixed point technique; multipoint boundary value problem; psi-Hilfer fractional derivative